PERANAN KEPOLISIAN DAERAH RIAU DALAM MELAKUKAN PENYIDIKAN KASUS TINDAK PIDANA YANG DILAKUKAN OLEH ANAK DIBAWAH UMUR - Tua, Jhon; A, Syaifullah Yophi; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Child protection in criminal law is very important, because children in the criminal law can be imposed on him, which can be penal sanctions or actions, which may affect mental development and soul, which can not be applied if or not achieving the target as a means to improve psychologist child. Children can be the subject of a criminal act caused by several factors, economic factors, environmental, community, family and educational background of both public schools and parents, and the application of religion in the family based on the data obtained by the authors of the children who committed the crime particularly sexual abuse is known that in 2011-2012 there were 21 children who committed the crime pencabulan.Tujuan Principal peneltian To determine the role of Riau police in investigating criminal cases are in children under lalukan by suspects under age And To determine the barriers facing regional police Riau in the investigation, to determine measures to be taken by the Riau Police in overcoming obstacles faced in conducting investigations in criminal cases which intervenes by suspected underage children. Terms of the method used, this study can be classified into types yuridisi sosilogis other research, because in this study the authors directly conduct research on location. This study conducted in Riau Police, sources of data used are secondary data, primary and tertiary techniques while collecting data through observation, interviews and study kepustaka. The collected data was then analyzed using the method of deductive qualitative analyzes of the problems of a general nature then specifically drawn to the conclusion based on existing theory. From the research, there are three main things that can be inferred. First Riau police role in investigating criminal cases committed minor First Implementation of an investigation into criminal offenses committed by minors in Riau Police have not run in accordance with the Criminal Procedure Code and Law No. 3 Year 1997 on Juvenile Justice, as in the execution there are still some obstacles Both barriers ditemi Riau police in investigating criminal cases minors ie, the difficulty of communication to the players, the difficulty of finding evidence and the absence of specific prisoners anak.Ketiga efforts made Riau police in overcoming obstacles encountered in carrying out the investigation of the criminal cases minors ie, calling a child psychologist, conducted the post mortem on the victim and submit a budget for the construction of juvenile detention.Keywords: Role – Investigation – Crime – Childrenunder